2015
DOI: 10.1016/j.ijid.2015.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-resistant and heteroresistant Mycobacterium tuberculosis and associated gene mutations in Ethiopia

Abstract: The prevalence of multidrug-resistant M. tuberculosis was high in the study area. Ser531Leu and Ser315Thr1 substitutions were the highest gene mutations for rifampicin and isoniazid, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
32
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 25 publications
9
32
2
Order By: Relevance
“…Likewise, reports from WHO [24], Ethiopia [7] and Northeast China [25] supports this finding. The reason for this might be due to social and health seeking behavior difference and higher exposure of males to outer environment, smoking and alcoholism [24].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Likewise, reports from WHO [24], Ethiopia [7] and Northeast China [25] supports this finding. The reason for this might be due to social and health seeking behavior difference and higher exposure of males to outer environment, smoking and alcoholism [24].…”
Section: Discussionsupporting
confidence: 70%
“…However, it was higher than studies observed in Ethiopia [8, 9, 31, 32], Kenya [33], Nigeria [34], Uganda [35] and South of Iraq [36]. In contrast, the proportion of rifampicin-resistant M. tuberculosis was lower than reports in other parts of Ethiopia [7, 36] and Chile [37]. The variation could be due to difference in risk for HIV acquisition, exposure to anti-TB drugs and national TB control program.…”
Section: Discussionmentioning
confidence: 65%
“…Before 20 years ago, reports showed that the prevalence of MDR-TB was almost nil or 1 % in different parts of Ethiopia [ 7 9 ]. Though, nowadays high proportion of MDR-TB were notified within the country [ 10 , 11 ]. It is well understood that bacterial and environmental factors play a great role in the spread of MDR-TB.…”
Section: Discussionmentioning
confidence: 99%
“…Detection of heteroresistance. Patients infected with a mixture of susceptible and resistant clones (heteroresistant clones) have been increasingly described in both MDR-TB and XDR-TB cases (47)(48)(49)(50). Detection of heteroresistance can be challenging for molecular assays; however, these mixtures of sequences may be detected as double peaks in T m -based detection systems (42).…”
Section: Resultsmentioning
confidence: 99%